Major antigenic proteins 1 and 2 of Cowdria ruminantium are targets for T-lymphocyte responses of immune cattle - Mwangi, David Miano; McKeever, Declan J.; Nyanjui, J.K.; Barbet, A.F.; Mahan, S.M. (Wiley, 1998)
Heartwater (cowdriosis) is an infectious disease of domestic ruminants in Africa and the Carribean and is caused by a tick-borne intracellular rickettsial agent, Cowdria ruminantium. There is growing evidence that immunity of cattle to the disease is medicated by T. lymphocytes. Antigens that stimulate these responses are therefore of considerable importance to the development of a sub-unit vaccine against heartwater. The genes which are of particular interest are examined, and the protein encoded by these genes are looked upon. Response to antigens is also discussed.